Analysis of the Development Strategy for the Palm Sugar Agroindustry in South Minahasa Regency - Grace A. J. Rumagit; Rine Kaunang; Charles R. Ngangi (Postgraduate, University of Mataram, 2026)
The development of the palm sugar agroindustry plays a crucial role in boosting the productivity and income of palm farmers. However, most palm farming operations have not yet been integrated into the processing industry. As a result, they are unable to increase farmers’ income. This study aims to: (1) examine and analyze the existing conditions of the palm sugar agroindustry system, (2) describe the EFI and EFE matrix factors of the palm sugar agroindustry system, (3) generate policy recommendations related to the development strategy of the palm sugar agroindustry. This study utilized primary and secondary data. Primary data were collected from 20 palm farmers purposive sampling, while secondary data were obtained from relevant agencies, journals, and publications related to the research. The results of the study show that the total score from the EFI analysis is 3.449 (strong), while the total score from the EFE analysis is 2.027 (weak). Strategies to strengthen and enhance farmers’ business opportunities include maintaining product variety and specifications to reach broader markets, as well as leveraging advancements in transportation and information technology by actively utilizing social media. To turn weaknesses into opportunities, farmers must use advanced production tools, market products to new regions, and retain loyal customers. To mitigate threats, farmers need to strengthen their position by increasing product variety, offering affordable prices, and expanding transportation infrastructure to support production and marketing. To address weaknesses and threats, palm sugar farmers must prioritize product quality to ensure it aligns with consumer preferences.